Myocardial Injury Predicts Risk of Short-Term All-Cause Mortality in Patients With COVID-19: A Dose–Response Meta-Analysis - Li, Yuehua; Pei, Hanjun; Zhou, Chenghui; Lou, Ying (Frontiers in Cardiovascular Medicine, 2022)
Objective Predictive value of myocardial injury as defined by elevated cardiac tropnins (cTns) in patients with COVID-19 has not been fully investigated. We performed a meta-analysis to evaluate the dose–response relationship between myocardial injury and short-term all-cause mortality. Methods Pubmed, Embase, and the Cochrane Library database were searched for all the studies which evaluated the relationship between cTns and the risk of short-term all-cause mortality in patients with COVID-19. Results Compared with patients without myocardial injury, the group with elevated cTns was associated with increased short-term mortality (11 studies, 29,128 subjects, OR 3.17, 95% CI 2.19–4.59, P = 0.000, I2 = 92.4%, P for heterogeneity 0.00). For the dose–response analysis, the elevation of cTns 1 × 99th percentile upper reference limit (URL) was associated with increased short-term mortality (OR 1.99, 95% CI 1.53–2.58, P = 0.000). The pooled OR of short-term mortality for each 1 × URL increment of cTns was 1.25 (95% CI 1.22–1.28, P = 0.000). Conclusion We found a positive dose–response relationship between myocardial injury and the risk of short-term all-cause mortality, and propose elevation of cTns > 1 × 99th percentile URL was associated with the increased short-term risk of mortality.